An in-depth study of molecular and supramolecular structures of bamboo cellulose upon heat treatment. (1st August 2020) - Lin, Qiuqin; Huang, Yuxiang; Yu, Wenji
Highlights: Heat treatment (≤200 °C) would not change the aggregation structure of bamboo cellulose. The break of glycosidic bonds during heating led to the reduction of crystallinity. Intermolecular hydrogen bonds in bamboo cellulose gradually dominated after heating. Abstract: In this study, two methods including a common method using high concentration of alkali solution and a mild extraction method at ambient conditions were used to extract cellulose from bamboo. The results showed that two methods affected the initial state of the cellulose. Celluloses obtained by the former was a hybrid of cellulose I and II while the latter was pure cellulose I. However, their heat treatment results indicated that the heat treatment (≤200 °C) would not change the aggregation structure of bamboo cellulose, but it will cause the change of intramolecular and intermolecular hydrogen bonds, and the break of glycosidic bonds in the amorphous region and part of the crystalline region of cellulose. Accordingly, the crystallinity of bamboo cellulose will decrease slightly after heat treatment. Finally, the macroscopic morphology change of bamboo cellulose caused by heat treatment was the thermal expansion in the width direction instead of distort.